PTH-069 Does Diverticulosis Protect Against Sigmoid Cancer?. (4th June 2013) - Tsiamoulos, Z P; Saunders, B P; Peake, S T; Nickerson, C; Rutter, M
Abstract : Introduction: With the advent of the English National Bowel Cancer Screening Programme (BCSP), a higher proportion of left-sided cancers than expected has been documented 1 . A high incidence of diverticular disease in the left colon has also been seen 2 . Anecdotally we observed that within the BCSP, relatively few sigmoid colon cancers were detected in people with sigmoid diverticulosis. Methods: An observational, retrospective analysis was performed of all BCSP FOB diagnostic colonoscopies between July 2007 and end June 2012. Patients reported to have sigmoid diverticulosis were identified and the incidence of colorectal cancer in the sigmoid colon was recorded. Chi sqaure with Yates correlation statistical analysis was performed with a p value of < 0.05 considered significant. Results: In the 5 year study period, 140, 459 BCSP colonoscopies were performed for a positive faecal occult blood (FOB) indication. Sigmoid colon cancers were found in 3.4% of procedures (n = 4738). Sigmoid diverticulosis was documented in 27.4% of procedures (n = 38480). Patients with sigmoid diverticulosis were less likely to have co-existing sigmoid colorectal cancer (3.99% of those patients without sigmoid diverticulosis had sigmoid colorectal cancer versus 2.23% of those patients with sigmoid colorectal cancer, p < 0.0001). Conclusion: This inverse association between sigmoid cancer and diverticulosis has not previously been reported but warrants further investigation. Potential explanations include increased likelihood of FOB positive result with diverticulosis (false positive; we consider this the most likely explanation), under-reporting of diverticulosis when a cancer is detected, missed lesions within the diverticular segment (unlikely, as for this to account for the difference this would mean almost half of sigmoid cancers being missed), or possibly a protective effect due to changes in bacterial flora in the diverticular segment. Further study in non-FOB populations is appropriate. Disclosure of Interest: None Declared. References: Logan RFA et al. Gut 2011 Almy TP et al. N Engl J Med 1980